1997
DOI: 10.1073/pnas.94.14.7543
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1a receptor gene expression in the heart: AP-1 and GATA-4 participate in the response to pressure overload

Abstract: Hypertrophy of mammalian cardiac muscle is mediated, in part, by angiotensin II through an angiotensin II type 1a receptor (AT 1a R)-dependent mechanism. To understand how the level of AT 1a Rs is altered in this pathological state, we studied the expression of an injected AT 1a R promoter-luciferase reporter gene in adult rat hearts subjected to an acute pressure overload by aortic coarctation. This model was validated by demonstrating that coarctation increased expression of the ␣-skeletal actin promoter 1.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
126
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(139 citation statements)
references
References 48 publications
(53 reference statements)
11
126
1
1
Order By: Relevance
“…There is evidence suggesting that ERK may function as a regulator of basal GATA-4 DNA binding activity, while p38 may mediate activation of GATA-4 by ET-1 . Transcription factor AP-1, in turn, is known to be a ubiquitous transcription factor whose binding sites are abundant in the promoter region of numerous cardiac genes (Herzig et al, 1997;Grepin et al, 1994). Previous studies have shown that MAPKs represent key upstream signalling molecules in many cell types, and they are able to activate AP-1 complex through a direct phosphorylation of the subunits .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence suggesting that ERK may function as a regulator of basal GATA-4 DNA binding activity, while p38 may mediate activation of GATA-4 by ET-1 . Transcription factor AP-1, in turn, is known to be a ubiquitous transcription factor whose binding sites are abundant in the promoter region of numerous cardiac genes (Herzig et al, 1997;Grepin et al, 1994). Previous studies have shown that MAPKs represent key upstream signalling molecules in many cell types, and they are able to activate AP-1 complex through a direct phosphorylation of the subunits .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, p38α-induced rBNP activation was not affected by the GATA-4 binding site mutation. Previous studies suggest functional cooperation between GATA-4 and AP-1 in pressure overload-induced hypertrophy (Herzig et al, 1997). To investigate the importance of AP-1 binding site in p38-induced BNP promoter activation, we introduced a site directed mutation at AP-1 binding site of rBNP promoter (BNP AP-1Mut).…”
Section: P38α and P38β Regulate Bnp Promoter Via Distinct Pathwaysmentioning
confidence: 99%
“…59 GATA4 is a transcription factor that regulates cardiacspecific genes during development. However, it has also been implicated in the development of cardiac hypertrophy 60,61 and mediates a variety of hypertrophic stimuli (see Liang and Molkentin 62 ). We did not observe any coding variants in GATA4.…”
Section: Discussionmentioning
confidence: 99%
“…8). In addition, previous studies showed that the AP-1 sites in the promoter regions were relevant to the pressure overload-mediated upregulation of cardiac AT1 receptor and atrial natriuretic factor genes (37,38). Furthermore, Ang II is a major factor in cardiovascular FN gene activation in vitro and in vivo, which seems to be different from FN gene regulation in other tissues.…”
Section: Functional Importance Of Rfn/ap-1 Element In Stretch-mediatementioning
confidence: 99%